How to make art at the end of the world : a manifesto for research-creation - Loveless, Natalie (Duke University Press, 2019)
Natalie Loveless examines the institutionalization of artistic research-creation--a scholarly activity that considers art practices as research methods in their own right--and its significance to North American higher education.